Hungarian Monitoring, 9 February 1988 . [Magyar rádiófigyelő], 1988. február 9 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - USSR: reception in Washington of Gorbachev's troop withdrawal plan; debate on ratifying missile treaty, contradictions of perestroika - Afghanistan: USSR regards formation of new Afghan coalition government as Afghan internal affair; Soviet Foreign Minister admits heavy losses - Money for the Polish economy, more Western capital help Domestic Affairs: - Situation in family support centers - Village meeting at future location of atomic waste - 1/3 of Budapest's roads are dirt roads: council plans own road building project - Evidence-saving operation at Gabčíkovo-Nagymaros construction site Economy: - Capitalist countries' central banks significantly raise credit amounts for East European countries - Valuing Ikarusz buses in hard currency instead of the ruble - Hungarian State Railway lacks orders Külpolitika: - SZU: Gorbacsov csapatkivonási tervének Washingtoni visszhangja;rakétaszerződés ratifikációs vitája, a peresztrojka ellentmondásai - Afganisztán: a SZU szerint az új afgán koalíciós kormány létrehozása afgán belügy; súlyos veszteséget ismert el a szovjet külügyminiszter - Pénz a lengyel gazdaságnak, ismét segít a nyugati nagytőke Belpolitika: - A családsegítő központok helyzete - Falugyűlés a paksi atomhulladék leendő helyén - A főváros útjainak egyharmada földút: önerős útépítést tervez a tanács - Leletmentő munkálatok a bős-nagymarosi építkezésnél Gazdaság: - A tőkés államok központi bankjai jelentősen emelték a kelet-európai országoknak nyújtott hitel összegét - IKARUSZ - Buszok értékesítése rubel helyett nyugati valutáért - Megrendelés híján a MÁV